Upconversion in low rare-earth concentrated phosphate glasses using direct NaYF4:Er3 +, Yb3 + nanoparticles doping. (October 2017) - Nguyen, H.; Tuomisto, M.; Oksa, J.; Salminen, T.; Lastusaari, M.; Petit, L.
Abstract: Upconversion (UC) was obtained from phosphate glasses which contain only 0.01 at.% of Er 3 + and 0.06 at.% of Yb 3 + . The glasses were prepared using direct doping method by adding NaYF4 :Er 3 +, Yb 3 + nanoparticles (NPs) into the glass at a doping temperature of 575 °C and 3 minute dwell time. The fraction of NP's survival during glass preparation can be augmented from 5 to 20% when replacing Na2 O by NaF in the glass. Our study suggests that the corrosion behavior of the glass melt is an important parameter to consider in order to engineer new NPs-containing glasses with high UC efficiency. Graphical abstract: